2006
DOI: 10.1002/mds.21104
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized brain network underlying postural tremor in Wilson's disease

Abstract: Common neurological manifestation of Wilson's disease (WD) is a postural tremor of the upper extremities. Recently, the primary sensorimotor cortex (S1/M1) has been shown to be involved in WD postural tremor generation. However, neuropathological changes in WD are mostly observed in subcortical structures. We therefore aimed to investigate whether S1/M1 may be functionally interconnected with other brain areas. In five WD patients, we used magnetoencephalography and surface electromyography (EMG) to record sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
(63 reference statements)
4
18
0
Order By: Relevance
“…In precise motor tasks, significant coherence has been shown between single units activity in deep cerebellar nuclei and local field potentials in primary motor cortex in monkeys [Soteropoulos and Baker, 2006]. In a MEG study on patients with Wilson's disease the tremor frequency related activity in primary motor cortex was significantly coupled with the activity of the ipsilateral thalamus and the contralateral cerebellum [Sudmeyer et al, 2006]. Therefore, our findings agree with previous evidence on a cerebellar effect on cortical EEG pattern that is mediated by thalamic nuclei.…”
Section: Discussionsupporting
confidence: 91%
“…In precise motor tasks, significant coherence has been shown between single units activity in deep cerebellar nuclei and local field potentials in primary motor cortex in monkeys [Soteropoulos and Baker, 2006]. In a MEG study on patients with Wilson's disease the tremor frequency related activity in primary motor cortex was significantly coupled with the activity of the ipsilateral thalamus and the contralateral cerebellum [Sudmeyer et al, 2006]. Therefore, our findings agree with previous evidence on a cerebellar effect on cortical EEG pattern that is mediated by thalamic nuclei.…”
Section: Discussionsupporting
confidence: 91%
“…Is there any correlation between the abnormalities in diffusion images and the clinical symptoms? Magnetoencephalographic data of symptomatic patients of WD have been published and demonstrated involvement of a cerebello-thalamo-cortical network in WD tremor generation [6, 30]. Sudmeyer et al showed strongly significant correlation between unified Parkinson's disease rating scale part III action tremor score and MRI signal change ratio in the head of the caudate nucleus, the globus pallidus, and the substantia nigra in patients of WD [10].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the gene, which is responsible for the synthesis of protein P-type ATPase (ATP7B), lead to pathological copper accumulation, especially in the liver and the brain [2]. Copper accumulation usually causes severe clinical manifestations, including liver failure, hepatitis [3], cirrhosis [4], premature death [5], and motor [6], emotion, cognitive impairments [7]. The neuropathological hallmark of the disease is neuronal loss and atrophy in lenticular nucleus, as well as in the midbrain [8], thalamus, and other parts of the basal ganglia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable clinical and neuroimaging data support the notion that this motor unit entrainment emerges from neuronal oscillation in the corticobulbocerebellothalamocortical loop [51•56], but the cause of oscillation in ET is unknown. Furthermore, oscillation in the corticobulbocerebellothalamocortical loop is not specific for essential tremor and also occurs in Parkinson disease [57], Wilson disease [58], rhythmic cortical myoclonus [59] and even voluntary tremor [60, 61]. …”
Section: Introductionmentioning
confidence: 99%